Obtenção e avaliação das atividades antiparasitárias de (±)-licarina a e alguns de seus derivados semissintéticos - Meleti, Vanderlisa Rita (2012)
This study describes the synthesis of (±)-licarin A (1, Scheme 1), a dihydrobenzofuran neolignan, by a reaction of oxidative coupling of isoeugenol with the enzyme Peroxidase from horseradish (HRP), according to methodology described in the literature. Afterwards, three semi-synthetic derivatives were obtained from this substance (Scheme 1): benzylated (±)-licarin A (2), (±)- methylated licarin A (3) and acetylated (±)-licarin A (4). After elucidation and assignments by Nuclear Magnetic Ressonance of 1H, 13C and DEPT, all compounds were evaluated in vitro against trypomastigote forms of Trypanosoma cruzi, the etiologic agent of Chagas disease. Thus, the compound 1 was the most active, as it showed an IC50 value of 100.8 µM. Another biologic assay perfomed was the schistossomicidal activity against Schistosoma mansoni adult worms. Regarding all neolignan evaluated, the acetylated (±)- licarin A (4) was the most active one, since it reduced adult worms motor activities, from the concentration of 25 µM, as well as, it caused the death of all worms in 50 µM and 100 µM within 120 hours and 24 hours, respectively.